Germatranes and carbagermatranes: (hetero)aryl and alkyl coupling partners in Pd-catalyzed cross-coupling reactions - Xu, Meng-Yu; Xiao, Bin (Chemical communications (Cambridge, England), 2021)
In the past few decades, palladium-catalyzed cross-coupling reactions have taken root in the construction of a complex synthetic community. The development of organometallics has been an important objective in this field. Our group has focused on exploiting new germanium-based reagents and the corresponding catalytic processes. In the past three years, we have established new methods for the synthesis of structure-modified (hetero)aryl germatranes and alkyl carbagermatranes. Particularly for alkyl carbagermatranes, the stability to be compatible with various derivatization reactions and the high activity for transmetallation ( e.g. base/additive-free for primary alkyl carbagermatranes) distinguish them from many reported nucleophiles. In this article, we would introduce (1) the development process of organogermanium reagents in palladium-catalyzed cross-couplings; (2) the history of germatrane-type systems and the breakthrough we have made in the field; (3) the outlook for (carba)germatranes and alkyl-GeMe 3 . The synthesis and Pd-catalyzed cross-couplings of structure-modified (hetero)aryl germatranes and alkyl carbagermatranes have been established.